The number of sick persons in a cohort. - Diehr, P; Derleth, A; Newman, AB; Cai, L (Research on Aging, 2007)
In the Cardiovascular Health Study, a cohort study of older adults followed up to 14 years, the number of sick persons was approximately constant over time. This was true whether we defined “sick” based on self-rated health, ADL or IADL difficulties, the timed walk, bed days, depression, cognitive problems, or cardiovascular disease. To better understand this phenomenon, we estimated the probabilities of transition among the healthy, sick, and dead states, and projected the number who would be in each health state over time for a birth cohort. The estimated number of sick persons in the birth cohort increased slowly over time and was approximately constant from ages 55-75, after which it decreased. The relative excess of older persons who are sick in later life is caused by a decline in the number of healthy persons rather than an increase in the number who are sick. Estimated total medical expenditures for a birth cohort may decline after about age 73. These findings may suggest a different way of thinking about trends in the health and medical expenditures of the population over time.
Keywords: Aging; equilibrium; transition probabilities; years of healthy life